TEACHER’S QUESTIONS IN EFL CLASSROOM - RITA ERLINDA; Sari Rahma Dewi (Ta'dib, 2014)
This study was addressed to explore types of questions and its frequency used by EFL teacher in the classroom during the teaching processes through analyzing the transcripts of the videotaped instructions. Another special emphasis is put on investigating the length of the students’ utterances in responding the teacher questions. The participants were 29 Grade-eleven students and  an English teacher. The results showed that rhetorical, procedural, closed, open, display, and referential questions were found, and it was more focused on the last four types of questions. However, display questions are more than twice as much as referential one, 50.8% compared to 14.6% occurrences, and closed questions are the most preferred questions with a total number of 252 which is also slightly more than double of referential questions which compose 62 questions. Conversely, open and referential questions produced longer students’ responses than closed and display ones.Key Words: teacher question, EFL classroom interaction, student responses